Open Source Data Management and Supervision System of an Isolated Microgrid in a Rural School - Guillermo R Catuogno; Guillermo O Acosta; Carlos G Catuogno (Revista Elektrón, 2021)
This paper presents the implementation of a data management system. The data is colleted from a wind-solar microgrid installed in a remote rural school. This system was made using free software, and consists of the acquisition of data from the wind-solar generator, the storage of the information in a relational database and the visualization of the information processed through the internet by means of a web browser. The developed system was installed in the Puerta del Sol area, located in the north of the province of San Luis and consists of a programmable logic controller (PLC) that collects the information of the process, a human-machine interface (HMI) screen for local visualization process data, and a computer that contains a web server and a database manager (located at the University facilities). An application programmed in Python runs in the computer and periodically queries the PLC via the internet about the process information and saves this information in a MariaDB database (MySQL compatible). At the same time, the web server responds through applications programmed in PHP language to the queries that, from a remote external client, are requested through an HTML page. The behavior of the proposed management system has been validated with the experimental results obtained.